Penggunaan Metode Pembelajaran Berbasis Edutainment dalam Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran IPS Di Kelas V MI NW Tenges-Enges: The Use of Edutainment-Based Learning Methods in Improving Student Learning Outcomes in Social Studies Subjects in Class V MI NW Tenges-Enges - Atika Zakiana; Baiq Ismi Azizah; Mursini; Irwan Yon Hadi (Pendidikan Al-Gafari, 2025)
Education is not merely trying to achieve learning outcomes, but how to obtain learning outcomes or processes that occur in children. Thus, in education, the process and learning outcomes must run in balance. This study aims to determine how to improve student learning outcomes through the use of edutainment-based learning methods in social studies subjects at MI NW Tenges-enges. The application of conventional methods is still widely applied in schools so that students find it difficult to understand social studies materials or subjects. The research method uses classroom action research (CAR) research conducted with a sample of 21 students in class V MI NW Tenges-enges. Data collection techniques use observation, interviews, student learning outcome tests, and documentation. The data analysis techniques are quantitative and qualitative. Based on the results of classroom action research conducted by researchers, the use of edutainment-based learning methods can improve student learning outcomes. It was obtained an increase in student learning outcomes in cycle I with an average value of 69.48 from 21 students, only 14 people got the complete category with classical completeness of 68.96% with the highest value of 90 and the lowest value of 60 and experienced an increase in cycle II with an average value of 80, where there were 14 students getting the complete category with classical completeness of 96.55%. So it is concluded that the increase in student learning outcomes from cycle I and cycle II increased by 25%.